Hinduism and Law : An Introduction - Lubin, Timothy; Davis Jr, Donald R.; Krishnan, Jayanth K. (Cambridge : Cambridge University Press, 2010)
Covering the earliest Sanskrit rulebooks through to the codification of 'Hindu law' in modern times, this interdisciplinary volume examines the interactions between Hinduism and the law. The authors present the major transformations to India's legal system in both the colonial and post colonial periods and their relation to recent changes in Hinduism. Thematic studies show how law and Hinduism relate and interact in areas such as ritual, logic, politics, and literature, offering a broad coverage of South Asia's contributions to religion and law at the intersection of society, politics and culture. In doing so, the authors build on previous treatments of Hindu law as a purely text-based tradition, and in the process, provide a fascinating account of an often neglected social and political history.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Hindu Law; Hinduism